1993
DOI: 10.1007/bf00320833
|View full text |Cite
|
Sign up to set email alerts
|

Crystal chemical variations in Ba-rich biotites from gabbroic rocks of lower crust (Ivrea Zone, NW Italy)

Abstract: Biotites from mafic rocks occurring at different stratigraphic levels of the Ivrea-Verbano Mafic Complex are studied. The rocks are gabbros and diorites. All the biotites are intermediate between phlogopite and annite [0.28 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…[25] The unit cell is outlined correlation between the chemical composition and the appearance of the 2M 1 polytype is known. [28] 3.1.1 | 27 Al and 17…”
Section: Phlogopitementioning
confidence: 99%
“…[25] The unit cell is outlined correlation between the chemical composition and the appearance of the 2M 1 polytype is known. [28] 3.1.1 | 27 Al and 17…”
Section: Phlogopitementioning
confidence: 99%
“…Thus, compositional control over long-range-ordered 3T stacking in trioctahedral micas appears to emerge at least for Li-rich compositions, but this stacking trend is not common in rock-forming, Li-poor biotite. In addition to the study by Baronnet et al (1993), 3T sequences with limited stacking order have been reported by TEM investigations in a H-poor, Fe-rich phlogopite from the Valle del Cervo (Italy) plutonic body (Bigi et al 1993;Bigi and Brigatti 1994), and in the H-poor and Fe 3+ -rich oxybiotites from the volcanic Ruiz Peak rhyodacites, New Mexico (Kogure and Nespolo 2001).…”
Section: Introductionmentioning
confidence: 96%
“…Although some authors maintained that chemical composi-* E-mail: r.fregola@geomin.uniba.it tion is not a likely factor controlling mica polytypism (Takeda and Ross 1975;Bigi et al 1993;Bigi and Brigatti 1994), others considered compositional variation itself a structural factor, thus playing a dominant role in controlling the formation of different mica polytypes (Smith and Yoder 1956;güven 1971). In addition, there are high-resolution and analytical transmission electron microscopy (HRTEM and ATEM, respectively) studies showing chemical differences among different coexisting stacking sequences (Baronnet and Kang 1989;Baronnet et al 1993;Xu and Veblen 1995).…”
Section: Introductionmentioning
confidence: 97%
“…Barium-rich micas are known from magmatic rocks (e.g. Bigi et al 1993;Edgar 1992;Gaspar, Wyllie 1982;Kogarko et al 2005;Mansker et al 1979;Thompson 1977;Wendlandt 1977;Zhang et al 1993), metamorphosed ore deposits (Chabu, Baulège 1992;Dasgupta et al 1989;Frimmel et al 1995;Frondel, Ito 1967;Gnos, Armbruster 2000;Holstam, Larsson 2000;Matsubara et al 1976;Yoshii et al 1973a, Tracy 1991 and metamorphic rocks (e.g. Bol et al 1989;Bucher-Nurminen 1982;Glassley 1975;Harlow 1995;Kretz 1980;Pattiaratchi et al 1967;Rice 1977;Solie, Su 1987;Tracy, Beard 2003).…”
Section: Introductionmentioning
confidence: 99%